2021
DOI: 10.3389/fcell.2021.803205
|View full text |Cite
|
Sign up to set email alerts
|

Targeting and Insertion of Membrane Proteins in Mitochondria

Abstract: Mitochondrial membrane proteins play an essential role in all major mitochondrial functions. The respiratory complexes of the inner membrane are key for the generation of energy. The carrier proteins for the influx/efflux of essential metabolites to/from the matrix. Many other inner membrane proteins play critical roles in the import and processing of nuclear encoded proteins (∼99% of all mitochondrial proteins). The outer membrane provides another lipidic barrier to nuclear-encoded protein translocation and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 159 publications
0
15
0
Order By: Relevance
“…1C), as already reported for other SARS-CoV-2 accessory proteins, such as ORF9b (Jiang et al, 2020). This latter was previously shown to directly interact with the outer mitochondrial membrane protein TOM70 (translocase of outer membrane 70) (Jiang et al, 2020), which forms the translocon complex with other TOM proteins (Eaglesfield & Tokatlidis, 2021). We found that hORF3c and bORF3c proteins colocalize with TOM70 and TOM20 (Suppl Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1C), as already reported for other SARS-CoV-2 accessory proteins, such as ORF9b (Jiang et al, 2020). This latter was previously shown to directly interact with the outer mitochondrial membrane protein TOM70 (translocase of outer membrane 70) (Jiang et al, 2020), which forms the translocon complex with other TOM proteins (Eaglesfield & Tokatlidis, 2021). We found that hORF3c and bORF3c proteins colocalize with TOM70 and TOM20 (Suppl Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it indicates that these proteins should be located on the mitochondrial membrane. Furthermore, these proteins carry MT peptide of ATP synthase δ subunit, which is a transmembrane protein in the mitochondrial inner membrane, so they should be led to the mitochondrial inner membrane via the TOM-TIM pathway [ 74 , 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…[29] However, it has been proposed that some tail-anchored and polytopic proteins are inserted into the OM in a spontaneous, lipid-assisted manner which needs further investigation. [30,31] The small Τims are a family of essential proteins of the intermembrane space, which bear twin CX3C motifs, and together with other cysteine-rich proteins, utilize the Mitochondrial Intermembrane space import and Assembly machinery (MIA) redox-based machinery to be properly targeted. This system consists of the oxidoreductase Mia40 which works together with the sulfhydryl oxidase essential for respiration and vegetative growth Erv1 (Augmenter of Liver Regeneration -ALR in mammals) to introduce intramolecular disulfide bonds in their substrate precursors.…”
Section: Overview Of the Yeast Mitochondrial Protein Import Systemmentioning
confidence: 99%